Sensory evaluation and pH of salad dressings treated by gamma radiation (Research, Society and Development, 2023)
The pH measurements of ready-to-eat salad dressings were evaluated to verify their stability against treatments with gamma radiation doses. Sensory analyzes of two salad dressings were conducted to verify consumer acceptance of salad dressings, treated by the process of irradiation by gamma rays, in the doses: 3 kGy and 5 kGy. The study protocol was carried out in two phases. In phase 1, the analyzes were conducted shortly after the samples were irradiated, which were close to their manufacturing dates. In phase 2, the samples were reassessed after a period of storage, close to their expiry date. The irradiation, in the absorbed doses studied, did not influence the pH and the results of the sensorial analysis indicated good acceptance of the irradiated sauces by the tasters.